THE ROLE OF SCHOOL LEADERSHIP IN DEVELOPING TEACHER PROFESSIONALISM - Wityastuti, Eva Zulvi; Hidayati, Dian; Suadirman, Siti Partini (Jurnal Visipena, 2025)
The role of school leadership is pivotal in fostering teacher professionalism, which directly influences the quality of education. However, challenges such as teacher resistance to change and limited motivation often hinder this effort. This study aims to explore effective school leadership practices in enhancing teacher professionalism through a literature review of four Scopus-indexed articles from 2020-2025. The study follows the PRISMA framework for article selection. Findings reveal that effective leadership is characterized by transformational, participative, transactional, and relationship-oriented styles. Among these, transformational leadership is the most dominant, as it aligns with the principal's vision to motivate and empower teachers. Strategies such as providing ongoing training, involving teachers in decision-making, offering performance-based rewards, and fostering emotional commitment were frequently applied. The study concludes that adaptive and collaborative leadership styles play a significant role in overcoming challenges and enhancing teacher professionalism, thus improving the overall quality of education.